3D polymer gel MRI dosimetry using a 2D haste, A 2D TSE AND A 2D SE multi echo (ME) T2 relaxometric sequences: Comparison of dosimetric results. (September 2016) - Maris, T.G.; Pappas, E.; Boursianis, T.; Kalaitzakis, G.; Papanikolaou, N.; Watts, L.; Mazonakis, M.; Damilakis, J.
Abstract : Introduction: Polymer gel dosimeters when exposed to ionising radiation increase their magnetic spin-spin relaxation rate (R2 = 1/T2) as a result of their polymerization. R2 can be measured with a variety of relaxometric MRI sequences and it is linearly correlated with the absorbed dose. Purpose: The aim of this study is to compare a 2D ME-HASTE, a 2D ME-TSE and a 2D ME-SE MR sequences in 3D MRI radiation dosimetry using N-vinylpyrrolidone (VIPAR) based polymer gels. Materials and methods: A 3D head mimicking patient phantom printed on a commercial 3D printer and 5 calibration glass vials were filled with VIPAR gel material and was irradiated to different radiation doses up to 40 Gy, using a 6 MV LINAC X-ray beam. The phantom and the vials were scanned using a 1.5 T whole body clinical scanner utilizing a 2D-ME-HASTE, a 2D-ME-TSE and a 2D-ME-SE relaxometric sequences. Correlations of R2 values with absorbed doses were estimated for all three sequences. Results: R2 (s −1 ) values, measured by either 2D ME sequence, were linearly correlated to absorbed dose (Gy) for the studied dose range. (R2: mean dose sensitivity 0.08 s −1 Gy −1, r : 0.99 p < 0.005). 2D-ME-HASTE sequences revealed the best anatomical coverage for the selected irradiation volume, the best SNR and the shortest scanning time. Conclusion: All 2D ME relaxometric sequences can be used for 3D MRI gel dosimetry using VIPAR gels. 2D-ME-HASTE sequences hold the absolute advantage of being a fast and the most reliable solution in VIPAR MRI gel dosimetry.